2016
DOI: 10.21037/atm.2016.11.06
|View full text |Cite
|
Sign up to set email alerts
|

During economic crisis can sleep questionnaires improve the value of oximetry for assessing sleep apnea?

Abstract: Background: The diagnosis of obstructive sleep apnea/hypopnea syndrome (OSAHS) is essential but polysomnography (PSG) is expensive and time consuming. Oximetry has been used as a less expensive indicator of OSAHS. The aim of the study was to evaluate the clinical utility of the combination of oximetry with four different questionnaires: Stop, Stop Bang (S-B), Berlin questionnaire (BQ), Epworth Sleepiness Scale (ESS) in order to identify patients at risk for OSAHS compared with in-laboratory PSG.Methods: Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, oxygen saturation or desaturation data were also regarded as simple and reliable indicators for sleep apnea-related conditions by some researchers. [17][18][19] We here found that, after taking into consideration many important clinical variables, all breathing indexes have a significantly positive or negative association with ESS scores in adults, except for mean oxygen saturation in older adults. We suppose that OSA might lead to EDS directly via poor sleep quality, tissue hypoxia, neuroinflammation, [20,21] or impaired macrovascular and microvascular endothelial function, [22] as well as indirectly via tissue damage from its related metabolic syndrome, [23] although sympathetic tone was elevated during sleep.…”
Section: Discussionmentioning
confidence: 97%
“…However, oxygen saturation or desaturation data were also regarded as simple and reliable indicators for sleep apnea-related conditions by some researchers. [17][18][19] We here found that, after taking into consideration many important clinical variables, all breathing indexes have a significantly positive or negative association with ESS scores in adults, except for mean oxygen saturation in older adults. We suppose that OSA might lead to EDS directly via poor sleep quality, tissue hypoxia, neuroinflammation, [20,21] or impaired macrovascular and microvascular endothelial function, [22] as well as indirectly via tissue damage from its related metabolic syndrome, [23] although sympathetic tone was elevated during sleep.…”
Section: Discussionmentioning
confidence: 97%